Ulnar artery–based free forearm flap: Review of specific anatomic features in 322 cases and related literature. Issue 8 (9th April 2014) - Hakim, Samer G.; Trenkle, Thomas; Sieg, Peter; Jacobsen, Hans‐Christian
Abstract Background The ulnar free forearm flap (UFFF) represents a variant of soft tissue transplants for orofacial reconstruction with specific topographic anatomy of the donor‐site, which has to be considered during flap raising. Methods Analysis of intraoperative findings during harvest of 322 UFFFs for head and neck reconstruction was performed. Harvest technique in view of variations of skin flap, vascular, and neuronal anatomy is described herein and related literature is reviewed. Results Aberrant superficial ulnar artery was observed in 1.5% of cases. The Martin–Gruber anastomosis was seen in 11.5%. The dorsal branch of the ulnar nerve was always visible and had to be dissected and separated under the flexor carpi ulnaris muscle and donor‐site morbidity was low. Conclusion Considering local anatomic features and variations, the harvest of the UFFF is safe and survival rates are comparable with those of the radial forearm flap. © 2014 Wiley Periodicals, Inc. Head Neck 36: 1224–1229, 2014